2016
DOI: 10.1038/srep35439
|View full text |Cite
|
Sign up to set email alerts
|

Electronically-Controlled Beam-Steering through Vanadium Dioxide Metasurfaces

Abstract: Engineered metamaterials offer unique functionalities for manipulating the spectral and spatial properties of electromagnetic waves in unconventional ways. Here, we report a novel approach for making reconfigurable metasurfaces capable of deflecting electromagnetic waves in an electronically controllable fashion. This is accomplished by tilting the phase front of waves through a two-dimensional array of resonant metasurface unit-cells with electronically-controlled phase-change materials embedded inside. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
114
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 43 publications
0
114
0
Order By: Relevance
“…The transition between these two phases often involves complicated atomic and electronic changes, the mechanism of which has long been a vibrant topic in condensed matter physics and material sciences [5][6][7]. More recently, the control of intermediate states in transitions has been explored for developing dynamically tunable antennae [8,9], beam steering metasurface [10], grayscale photolithography [11] and multi-level memory [12].…”
Section: Introductionmentioning
confidence: 99%
“…The transition between these two phases often involves complicated atomic and electronic changes, the mechanism of which has long been a vibrant topic in condensed matter physics and material sciences [5][6][7]. More recently, the control of intermediate states in transitions has been explored for developing dynamically tunable antennae [8,9], beam steering metasurface [10], grayscale photolithography [11] and multi-level memory [12].…”
Section: Introductionmentioning
confidence: 99%
“…As the two dimensional equivalent of bulk metamaterials, metasurfaces have caused considerable attention in recent years due to ultra‐thin thickness, lower profile, and simpler to fabricate . Yu et al firstly demonstrated a two‐dimensional nano‐antenna metasurface to control the beam reflection and refraction.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al firstly demonstrated a two‐dimensional nano‐antenna metasurface to control the beam reflection and refraction. Recently, the methods of controlling antenna beam direction by using metasurfaces have been investigated . Chen et al theoretically analyzed an antenna can exhibit continuous scanning capability by controlling the phase properties of a metasurface radome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another characteristic that makes VO 2 a promising tunable material is that the switching time is very fast when changing from a semiconductor property to a metal property. The study of VO 2 is mainly focused on two areas: the first design idea is changing the electrical length by exploiting the ultra-large change of the refractive index in VO 2 between the semiconductor and the metallic states [21][22][23], and the second design idea is changing the transverse electric and transverse magnetic pass with different phases [24,25]. However, these two ideas are still far from achieving full control over the electromagnetic wave.…”
Section: Introductionmentioning
confidence: 99%